Metal Nanoapertures and Single Emitters. Issue 20 (26th August 2020) - Gordon, Reuven
Abstract: Nanoapertures in metal films have long been recognized for their ability to confine light to subwavelength dimensions. This allows for high‐resolution imaging of single emitters with enhanced emission rates. It also provides a background‐free environment that has been exploited for biophysical applications like fluorescence correlation studies at high physiological concentrations and DNA sequencing. Recently, other advantages of single apertures have been recognized, including optical trapping, thermal management, and nanofluidic (nanopore) functionality. This paper reviews metal nanoapertures and their applications to single emitter studies for biophysical and quantum applications. Abstract : Apertures in metal films isolate single emitters at the extreme subwavelength scale, allowing for capturing photons from a single emitter and monitoring interactions. The metal aperture can provide the additional benefits of field enhancement, thermal management, optical tweezing, nanofluidic functionality and directivity. This has led to applications in biophysics and single photon sources, with commercial devices existing.